The Influence of Operation Temperature and Variations of the Illumination on the Performance of Integrated Photoelectrochemical Water‐Splitting Devices. Issue 8 (10th May 2017) - Welter, Katharina; Smirnov, Vladimir; Becker, Jan‐Philipp; Borowski, Patrick; Hoch, Sascha; Maljusch, Artjom; Jaegermann, Wolfram; Finger, Friedhelm
Abstract: Renewable and storable fuel hydrogen can be produced through light‐driven water splitting using photovoltaic‐biased electrosynthetic (PV‐EC) devices. The required voltage to drive the reaction is approximately 1.5 V, which can be provided using multi‐junction silicon solar cells. To generate these voltages at the operation point, the solar cells are electrically optimized with respect to the standard test conditions. However, if such devices were to be used outdoors, a wide range of different illumination conditions has to be considered. Herein, we discuss the dependence of the solar‐to‐hydrogen efficiency on the spectral quality, the incident illumination intensity and the operation temperature. It is found that in the case of high irradiation intensities (e. g. 1 sun), high operation temperatures reduce the PV performance, but the overall PV‐EC device performance remains almost unchanged due to improved kinetics in the EC part. In contrast, when the illumination intensity is reduced, the loss in PV performance cannot be compensated by improved EC performances due to higher temperatures. Abstract : There's no such thing as bad weather : Photovoltaic‐biased electrochemical (PV‐EC) devices based on multi‐junction thin‐film silicon solar cells are investigated under conditions different from standard test conditions and similar to conditions obtained outdoors. We discuss how the performance of the PV‐EC device is influenced by spectral quality, illumination intensity and operation temperature.